المختلف و المؤتلف في الأمثال الشعبية بين وادي سوف و تبسة - جريبيع، مفيدة, مساني، محمد (جامعة الوادي University of Eloued, 2019)
الملخص: مما لاشك فيه أن للجانب العقلي و الاجتماعي دور كبير في طرق التفكير و التعبير كما للتجارب و المعارف اسهام كبير في البناء الثقافي والحضاري وبحسب التقدم يكون الابداع بأشكال وألوان وفروع مختلفة و على أقساط وفيرة تنقسم بين المادي و المعنوي فتحمل في طياتها أبعادا عقلية و نفسية وأفاق اجتماعية و دينية و أخلاقية لها صلات عميقة بالعادات والتقاليد وكل أنواع التعبير وهو ما وجد في الأدب الشعبي بكل ضروبه و جوانبه وأنواعه و حيثياته المختلفة و خاصة منها المثل الشعبي لمنطقتي وادي سوف وتبسة . ولذا فمن الواجب علينا القيام بأحياء هذه الثقافة المتمثلة في الموروث المخزون في الذاكرة الشعبية الجماعية من حكايات وألغاز و أمثال ... الخ فهذه المأثورات هي التي تصور النضج الفكري و الأخلاقي للأمة وعلى هذا الأساس حاولنا جمع ما يمكن جمعه من الأمثال الشعبية المحلية الخاصة بمنطقة وادي سوف و تبسة و دراستها و موازنتها و ذكر أهم أوجه الاختلاف و التشابه بين أمثال المنطقتين . وقد رسمنا خارطة فصول على النحو التالي مدخل: تم التطرق فيه الى الاطار العام لمنطقتي البحث وادي سوف و تبسة الفصل الأول: احتوى على هوية المثل الشعبي من مفهوم ومرجعية وأنواع و خصائص وأهمية ودور الفصل الثاني: وهو الفصل التطبيقي وتم فيه القيام بموازنة من حيث الموضوع بين الأمثال الشعبية السوفية والتبسية اضافة الى المختلف والمؤتلف في الأمثال الشعبة بين المنطقتين وختم البحث بجملة من النتائج المتوصل اليها اضافة الى ملحق يحتوي على أهم الامثال الشعبية لكلتا المنطقتين تبسة ووادي سوف. Résumé : فرنسية أو انجلزية There is no doubt that the mental and social side plays a major role in the ways of thinking and expression, as well as experiments and knowledge. A great contribution to cultural and civilizational construction. According to progress, creativity is in different forms, colors and branches, and in large installments, divided between material and moral, Social and religious and moral links with deep customs and traditions and all kinds of expression, which is found in folk literature in all its different aspects and types and different aspects, especially the popular example of the regions of Wadi Suf and Tabsa. Therefore, it is incumbent upon us to carry out the life of this culture, which is the legacy of the collective folk memory of tales, puzzles, etc. These are the events that depict the intellectual and moral maturity of the nation and on this basis we tried to collect what can be gathered from the popular local proverbs of Wadi Will study and study and balance and mention the most important differences and similarities between the two regions. We have drawn a map of chapters as follows Entrance: The general framework of the research areas Wadi Suf and Tebessa was discussed Chapter 1: The identity of popular ideals of concept, reference, types, characteristics, importance and role Chapter II: the applied chapter in which a balance was made in terms of the topic between the popular Sufi Supremacy and prayer, in addition to the different and recited in the parables between the two regions The research concludes with a set of results, as well as an appendix containing the most popular proverbs of both Tepsa and Wadi Suf.
Keywords: الأمثال الشعبية - تبسة- واد سوف-الموردين